2003
DOI: 10.1523/jneurosci.23-01-00260.2003
|View full text |Cite
|
Sign up to set email alerts
|

Signaling by Bone Morphogenetic Proteins and Smad1 Modulates the Postnatal Differentiation of Cerebellar Cells

Abstract: Previous studies have demonstrated that bone morphogenetic proteins (BMPs) activate the Smad1 signaling pathway to regulate cell determination and differentiation in the embryonic nervous system. Studies examining gene and protein expression in the rat cerebellum suggest that this pathway also regulates postnatal differentiation. Using microarrays, we found that Smad1 mRNA expression in the cerebellum increases transiently at postnatal day 6 (P6). Immunohistochemistry and Western blots showed that Smad1 and BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 48 publications
2
64
0
Order By: Relevance
“…Numerous experiments in a variety of in vitro models have demonstrated that multiple BMPs, used individually or in various combinations can induce the differentiation of a wide variety of tissues including bone, cartilage, adipose tissue, and muscle [4,8,21,22]. BMP-2 and BMP-7 have further been demonstrated to enhance bone healing in vivo in animals and humans in settings such as spinal fusion, fracture repair and distraction osteogenesis [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous experiments in a variety of in vitro models have demonstrated that multiple BMPs, used individually or in various combinations can induce the differentiation of a wide variety of tissues including bone, cartilage, adipose tissue, and muscle [4,8,21,22]. BMP-2 and BMP-7 have further been demonstrated to enhance bone healing in vivo in animals and humans in settings such as spinal fusion, fracture repair and distraction osteogenesis [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown whether some GCPs also develop into astroglial cells in vivo. Although it has been shown that both Shh (12)(13)(14) and BMPs (23,33) are expressed in Purkinje cells and in the EGL, it is not known whether the levels of these proteins are sufficient to induce some GCPs to develop into astroglial cells. Such differentiation could easily be missed because only a small proportion of GCPs are induced to become astroglial cells in culture by Shh and BMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results suggest that immature GCPs treated with Shh-N and BMP2 differentiate first into the GFAPand neuronal marker-positive cells and then finally into GFAPpositive, S100-␤-positive, neuronal marker-negative, and differentiated astroglial cells. initiate the program of granule cell specification, and Angley et al (23) provided evidence that BMP4 might participate in regulating postnatal granule cell and astroglial cell differentiation. Several laboratories have shown that Shh produced and released by Purkinje cells is a potent mitogen for GCPs (12)(13)(14)(15)24).…”
Section: Some ''Switching Cells'' Coexpress Neuronal and Astrocyte Mamentioning
confidence: 99%
See 1 more Smart Citation
“…Hindbrain roof plate cultures express Bmp6, Bmp7, and Gdf7 and these factors are sufficient to induce cerebellar granule neurons (Alder et al 1999;Machold et al 2007). BMP-4 and BMP-6 stimulate differentiation and promote survival of granule neurons (Angley et al 2003;BarnedaZahonero et al 2009), whereas targeted inactivation of Bmpr1a and Bmpr1b in mice results in fewer cerebellar granule neurons, causing a smaller cerebellar cortex without foliation (Qin et al 2006). Application of noggin to the developing midbrain -hindbrain border results in complete loss or dorsal shift of Phox2-positive neurons.…”
Section: Tgf-b and Neural Developmentmentioning
confidence: 99%